Calcification and Airway Stenosis in a Neonate with Chondrodysplasia Punctata - Garge, Saurabh (Journal of Neonatal Surgery, 2019)
Chondrodysplasia punctata (CDP) is a group of congenital bone and cartilage disorders. Laryngeal and tracheal calcification and subsequent stenosis are not frequently seen. We report here a case of an infant with CDP associated with tracheal stenosis.